Media Partisanship and Fundamental Corporate Decisions. (26th March 2022) - Knill, April; Liu, Baixiao; McConnell, John J.
Abstract: Using the introduction of Fox News as a natural experiment, we investigate whether partisanship in television news coverage influences fundamental corporate decisions. We find that during the George W. Bush presidency, firms led by Republican-leaning managers headquartered in regions into which Fox was introduced shift upward their total investment expenditures and financial leverage. Our findings imply that in making fundamental corporate decisions, Republican-leaning managers are swayed by the Republican slant of Fox that presents an optimistic macroeconomic outlook. The results highlight the importance of heterogeneity in media slant in understanding the role of the media in corporate decision making.